Pemberdayaan Masyarakat Melalui Edukasi dan Pemeriksaan Payudara Sendiri (SADARI) sebagai Upaya Pencegahan Dini Kanker Payudara di Desa Bentakan, Baki, Sukoharjo - Wimpy; Endang Widhiyastuti; Astri Aditya Wardhani; Yusuf Gesha Kesumawijaya; Nathania Thea Vashty Dwi Andiny; Nur Fadilah; Dewi Kumalasari; Vindy Widya Kusumaning Tyas (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Breast cancer has the highest incidence among women in Indonesia and remains a leading cause of cancer-related mortality, especially in rural areas with limited health education and low awareness of early detection. This community service program aimed to improve knowledge and skills of Breast Self-Examination (BSE) in Bentakan Village, Sukoharjo. The program involved 26 women of reproductive age and health cadres through education, interactive discussion, and hands-on practice using breast models. Evaluation was conducted using pre-test and post-test with knowledge categorization and paired sample t-test analysis. The results showed a shift in knowledge distribution, where poor knowledge decreased from 61.5% to 0% and good knowledge increased from 0% to 69.2%. Paired sample t-test analysis confirmed a significant increase in knowledge (p < 0.001). This program effectively improved community awareness and skills in early breast cancer detection.